2020
DOI: 10.3390/ani10111948
|View full text |Cite
|
Sign up to set email alerts
|

The Comparison of Semen Collection in Electroejaculation, Rectal Massage and Combination of Both Methods in the Critically Endangered Malayan Pangolin, Manis javanica

Abstract: This article describes the semen characteristics from different collection methods between captive and confiscated Malayan pangolins, Manis javanica. Semen was collected from 15 pangolins; two captive and 13 confiscated individuals at the mean weight of 9.36 ± 1.94 kg. The three semen collection methods employed were electroejaculation, rectal massage and a combination of both techniques. The semen characteristics (mean ± standard deviation) of the Malayan pangolin are volume (73.75 ± 144.57 µL), pH (7.63 ± 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…The collection of banteng semen by the transrectal massage method has not been previously reported. This method has been used in swamp buffalo (Bubalus bubalis), rhinos (Dicerorhinus sumatrensis), elephants (Elephas maximus), and pangolins (Manis javanica) (Arifiantini and Ferdian 2006;Agil et al 2008;Kiso et al 2013;Tarmizi et al 2020). The volume of banteng semen in this study was less than the semen volume successfully collected by electroejaculation reported in previous studies (Yoelinda et al 2018).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The collection of banteng semen by the transrectal massage method has not been previously reported. This method has been used in swamp buffalo (Bubalus bubalis), rhinos (Dicerorhinus sumatrensis), elephants (Elephas maximus), and pangolins (Manis javanica) (Arifiantini and Ferdian 2006;Agil et al 2008;Kiso et al 2013;Tarmizi et al 2020). The volume of banteng semen in this study was less than the semen volume successfully collected by electroejaculation reported in previous studies (Yoelinda et al 2018).…”
Section: Discussionmentioning
confidence: 66%
“…Research by Abril-Sánchez et al (2017) shows that this method is less stressful. Furthermore, several studies have shown that the quality of semen, especially microscopically, obtained by an electro-ejaculator is not significantly different from that of transrectal massage (Sarsaifi et al 2013;Tarmizi et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon is shared by other species, including camelids [ 23 , 28 ], elephants [ 18 , 34 ], hippopotamus’ [ 19 ] and primates [ 21 , 22 ]. Spermatozoa trapped within the viscous (low sperm) fractions of the ejaculate equate to almost half of the total spermatozoa collected [ 11 , 17 , 20 ], but are often discarded. In the current study, treatment of viscous, low sperm rhinoceros spermatozoa, with papain prior to cryopreservation, not only enabled the utilisation of spermatozoa within these fractions, but resulted in improved motility and viability post-thaw.…”
Section: Discussionmentioning
confidence: 99%
“…It would also be interesting to see if this protein is conserved across other species of rhinoceros, such as the critically endangered black [ 48 ], Sumatran [ 49 ] and Javan [ 50 ] rhinoceroses and vulnerable greater one-horned rhinoceros [ 51 ], particularly the Sumatran rhinoceros, given less than 30 individuals remain, and all published reports of semen collection report severely low sperm counts and volume [ 39 , 52 ]. Similarly, comparison against the seminal plasma proteome of the hippopotamus [ 19 ], elephants [ 20 , 35 ] and primates [ 22 ] would show whether this protein is responsible for causing the production of viscous fractions across a wide variety of species. More so, it would confirm whether papain could be used as a tool to improve the quantity and quality of spermatozoa collected and cryopreserved from wildlife species following electro-ejaculation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation